Analysis of the decisions of foreign regulatory authorities - Relevant information (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2019)
Analysis of  recommendations of  foreign regulatory authorities on  the  restriction of  circulation of medicines and/or the  need  for  changes in the  instructions for  their medical use  due  to changes in the safety profile, conducted by experts of the Scientific Centre for Expert Evaluation of Medicinal Products revealed 25 administrative decisions of foreign regulatory authorities. These  decisions contained information on the  following medicines registered in Russia: apixaban, granulocyte-macrophage colony  stimulating factor, hydroxyethyl starch, dabigatran, eltrombopag, epoetin alfa, atypical antipsychotic drugs, benzocaine, varenicline, carbamazepine, lamotrigine, suvorexant, topiramate, aztreonam, azithromycin, isoniazid, caspofungin, miconazole, meropenem, atazanavir, dolutegravir, lamivudine, efavirenz.